PENGARUH PENGETAHUAN PERPAJAKAN, PELAYANAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BENDAHARA DILINGKUNGAN BADAN NARKOTIKA NASIONAL - Sigit Herdianto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to determine and analyze the effect of tax knowledge, tax services and tax sanctions on treasury taxpayer compliance in the National Narcotics Board. The research design used in this study is a descriptive method with a qualitative method approach. Hypothesis Results Partial Test (t) Testing the first hypothesis (H1) states that taxation knowledge does not have a significant effect on taxpayer compliance. Based on statistical parameters, the t-count value is 0.731 <2.056 (t-table). At a significance of 5% (0.05), it is said that knowledge of taxation has no effect on taxpayer compliance. The second hypothesis testing (H2) states that taxation services do not have a significant effect on taxpayer compliance. Based on statistical parameters, the value of tcount is -0.292 <2.056 (t table). At a significance of 5% (0.05), it is said that taxation services have a negative and insignificant effect on tax compliance of taxpayers. Testing the third hypothesis (H3) states that tax sanctions have no significant effect on taxpayer compliance. Based on statistical parameters, the value of tcount is -1,955 <2,056 (ttabel). At a significance of 5% (0.05), it is said that the size of tax sanctions has a negative and insignificant effect on tax compliance of taxpayers. Hypothesis Test Results on the Coefficient of Determination (R2), the R2 value of this study is 0.198, this value means that the total dependent variable is related to an average of 19.8%. It can be explained by the relationship between tax knowledge, tax services, and tax penalties. Together. While the remaining 80.2% is influenced by other factors that are not explained in this study.